PENGARUH CASH HOLDING, DER, DPR DAN NPM TERHADAP INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013 -2016 - Faizal Gazali DM; Muhammad Ali; Andi Aswan (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the effect of Cash Holding, Debt to Equity Ratio, Dividend Payout Ratio Net Profit Margin, to Income Smoothing. This research design using logistic regression method using data based on financial statements of manufacturing companies listed on the BEI in the period 2013-2016 published by BEI on the internet. Data selected by using purposive sampling method. Data analysis techniques use the SPPS ver 25 program. The eckel index is used to calcify companies that do and do not practice income smoothing. Based on the results of research only cash holding has a positive and significant influence and in accordance with the theory of income smoothing practices conducted by the company, it attracts to variable debt to equity ratio has a negative and significant effect on the practice of income smoothing conducted by the company, while dividend payout ratio (DPR ) and net profit margin (NPM) does not have an influence on the practice of income smoothing by the company.